In Vitro and In Vivo Effects of Ketamine on Generation and Function of Dendritic Cells - Jingxian Zeng; Shuxuan Xia; Wa Zhong; Jie Li; Liling Lin (Elsevier, 2011)
Abstract.: The question about how intravenous anesthetic reagents affect the development and function of dendritic cell subsets still has no comprehensive answers. Bone marrow cells differentiated with FMS-like tyrosine kinase 3 ligand in vitro represented the steady-state dendritic cell subsets. The effects of ketamine on the generation and function of dendritic cell subsets were investigated. We found that dendritic cell subsets responded to the anesthetic reagent ketamine in several aspects: 1) The in vitro and in vivo development of plasmacytoid dendritic cells were inhibited by ketamine at high concentrations; 2) The endocytosis of dendritic cells were not influenced by ketamine at concentrations from 50 - 200 μM; 3) The maturation markers of conventional dendritic cells were not changed by ketamine upon LPS or CpG stimulation, although the cytokines mRNA profiles were affected; 4) The allogenic-stimulatory activity of dendritic cells was suppressed by ketamine. In conclusion, ketamine hampered plasmacytoid dendritic cell subset development both in vivo and in vitro. The dendritic cells maturation and downstream responses towards different toll-like receptor stimuli were differently regulated by ketamine treatment. Keywords:: anesthesia, ketamine, dendritic cell, plasmacytoid dendritic cell, conventional dendritic cell